Features of characteristics of character of modern ukrainian parents (Actual Problems of Psychology in Educational Institutions, 2019)
The article presents the characteristics of the characteraccentuation of the personality of modern Ukrainian adolescents. The authorinvestigates the role of characterological features, in particular characteraccentuation, in the process of personal formation of adolescents. Analyzes themajor classifications of accentuations by H. Schmieschek. The importance ofcharacter accentuations in the predictor structure of students' frustrationresponse profiles is revealed. Testing of students of middle classes, namelyadolescence. The obtained data identified the types of character accentuations,which are students. Also, with the help of testing, it is established what type ofcharacter accentuation is the most common among modern adolescents.